2019
DOI: 10.21769/bioprotoc.3221
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Oxidative Stress Protocols for Low-microliter Volumes of Mammalian Plasma

Abstract: Small blood volumes commonly obtained from small mammals during field studies are only sufficient for a single biochemical assay. In this study, we used blood collected from a population of wild eastern chipmunks (Tamias striatus) and developed modified methods to improve analytical selectivity and sensitivity required for measuring markers of oxidative stress using small blood volumes.Specifically, we proposed a modified malondialdehyde (MDA) analysis protocol by high performance liquid chromatography (HPLC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Previous studies showed that the ROS act as a trigger that switch on the NLRP3 inflammasome and contribute to disease progression in a vicious cycle [54]. In accord with previous studies, we found that MLR increased in RA patients compared to the healthy-matched group [29]. Our study revealed that MLR has an increased accuracy compared to NLR, to an AUC of 0.93, and 95% CI between 0.82 and 1.03, as a result of ROC analysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies showed that the ROS act as a trigger that switch on the NLRP3 inflammasome and contribute to disease progression in a vicious cycle [54]. In accord with previous studies, we found that MLR increased in RA patients compared to the healthy-matched group [29]. Our study revealed that MLR has an increased accuracy compared to NLR, to an AUC of 0.93, and 95% CI between 0.82 and 1.03, as a result of ROC analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Blood cells were removed from the plasma immediately following centrifugation. Plasma aliquots were properly stored (at −80 • C, with avoiding repeated freezing/refreezing cycle) for further analysis of oxidative stress markers, these are in accord with other studies that showed the sample stability for oxidative stress markers in biological fluids (for 1 year at −80 • C or two days at 4 • C) [29,30]. For inflammatory markers, venous blood samples were collected on a vacutainer from Becton Dickinson (BD) and the blood was allowed to clot for 20 min at room temperature (RT).…”
Section: Sample Collectionsupporting
confidence: 74%
See 1 more Smart Citation